Security Aspects of Improvised Explosive Devices. The Ukrainian Case Study (Global Journal of Human-Social Science, 2023)
Though Improvised Explosive Devices IEDs are commonly attributed to attacks carried out by terrorists in the Middle East IEDs were also used in the Ukrainian conflict and extremely limited research touches upon the issue There is a hypothesis that IED events were not mainly focused on killing but rather on striking terror and sowing chaos among the local populace to persuade it to withdraw its support for the Ukrainian government This article presents an analysis of IEDs as a unique weapon the possible intensions behind their occurrence in Ukraine at a particular point in time and the methods of identifying IED use in Ukraine based on the Global Terrorism Database GTD and the authors database TAD Both the imprecision and uncertainty relative to GTD s classification were discussed as it served only as the starting point for data evaluation yielding informative results although containing little information related to the IEDs directly
Keywords: Ukrainian security; armed conflict; terrorism; terrorist attacks; improvised explosive device (IED)